Implementation of a New Contactless Piezoelectric Wind Energy Harvester to a Wireless Weather Station - Uzun, Y.; Demirbas, S.; Kurt, E. (Elektronika ir Elektrotechnika, 2014)
A newcontactless piezoelectric (PZT) wind energy harvester is constructed and a feasibility study on its power generationmechanism is carried out for a wireless weather station. The new harvester has a magnetic unit enabling to vibrate aPZT layer in a contactless manner. The poles of magnets are oriented in such a way that the tip of the layer is always repelled, when wind rotates the harvester shaft. Therefore the produced magnetic force exerts mechanical bucklings on the layer and this effect produces electricity. After one-year operation, it is clarified that an averaged power of 20 µW–60 µW can be obtained monthly for the feeding of the station. These results prove that 5 %–18 % of the consumed power of wireless station can be generated by the harvester depending on the wind regime in the region. DOI: http://dx.doi.org/10.5755/j01.eee.20.10.8871